The risk sensitivity of global liquidity flows: Heterogeneity, evolution, and drivers - Stefan Avdjiev; Leonardo Gambacorta; Linda S. Goldberg; Stefano Schiaffi (Federal Reserve Bank of New York, 2025)
The period after the Global Financial Crisis (GFC) was characterized by a considerable risk migration within global liquidity flows, away from cross-border bank lending towards international bond issuance. We show that the post-GFC shifts in the risk sensitivities of global liquidity flows are related to the tightness of the balance sheet (capital and leverage) constraints faced by international (bank and nonbank) lenders and to the migration of borrowers across funding sources. We document that the risk sensitivity of global liquidity flows is higher when funding is provided by financial intermediaries that are facing greater balance sheet constraints. We also provide evidence that the post-GFC migration of borrowers from cross-border loans to international debt securities was associated with a decline in the risk sensitivity of global liquidity flows to EME borrowers.
Keywords: G10; F34; G21; 330; global liquidity; international bank lending; international bond flows; emerging markets; advanced economies